USEPA Develops National Water Reuse Action Plan. Issue 7 (1st July 2020) - Adams, Hunter; Southard, Mark; Nix, Daniel
Abstract : "Water reuse represents a major opportunity to support our nation's communities and economy by bolstering safe and reliable water supplies for human consumption, agriculture, business, industry, recreation, and healthy ecosystems." —US Environmental Protection Agency Administrator Andrew Wheeler